2011
DOI: 10.1038/labinvest.2011.74
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking alters epithelial apoptosis and immune composition in murine GALT

Abstract: Smokers have a twofold increased risk to develop Crohn's disease (CD). However, little is known about the mechanisms through which smoking affects CD pathogenesis. Especially Crohn's ileitis is negatively influenced by smoking. Interestingly, the ileum and, more in particular, the Peyer's patches in the terminal ileum are also the sites where the first CD lesions are found. Several chemokines are implicated in the pathogenesis, among which is the CCL20-CCR6 pathway. Here, we studied the gut-associated lymphoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 52 publications
2
57
0
2
Order By: Relevance
“…There is strong evidence that cigarette smoke exposure leads to the accumulation of Tregs in respiratory airways in mice 34 and humans 35 as well as in the gut epithelium of exposed mice. 36 Elevated blood Treg numbers may reflect the mobilization and trafficking of Tregs into cigarette smoke exposed tissues. This is biologically plausible given the fact that cigarette smoking is associated with increases in the expression of the Treg chemoattractants CCL2 and CCL22.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence that cigarette smoke exposure leads to the accumulation of Tregs in respiratory airways in mice 34 and humans 35 as well as in the gut epithelium of exposed mice. 36 Elevated blood Treg numbers may reflect the mobilization and trafficking of Tregs into cigarette smoke exposed tissues. This is biologically plausible given the fact that cigarette smoking is associated with increases in the expression of the Treg chemoattractants CCL2 and CCL22.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model, we have demonstrated that, similarly to the lung, CS affects the gut immune system by enhancing the recruitment of CD11b+ DCs, CD4+ and CD8+ T cells to the mouse ileal Peyer's patches, which are the main lymphoid organs in the gut [142]. Furthermore, CS alters the production of immune factors in the mouse ileum (increased CXCL2, an IL-8 homolog) and in the proximal colon (increased IL-6) [138].…”
Section: Impact Of Cs On Trp Channels In the Gut?mentioning
confidence: 99%
“…We recently demonstrated that chronic CS exposure induces apoptosis in the FAE. We suggested that this is due to oxidative stress associated with smoking (Verschuere et al 2011). In the present study, we examined the presence of autophagic vesicles in the FAE of air-and CS-exposed mice and we analyzed the size and number of these vesicles by means of transmission electron microscopy.…”
Section: Introductionmentioning
confidence: 97%